2015
DOI: 10.4317/jced.51875
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lichen planus among a sample of the Egyptian population

Abstract: Objectives: To report on the prevalence of oral lichen planus among a sample of the Egyptian population. Study Design: 4470 Egyptian patients, aged 15-75 years, were seen at the outpatient clinic at the Faculty of Oral and Dental Medicine, Cairo University, Egypt. 31.25 % of these patients were males and 68.75% were females. Oral mucosal lesions consistent with oral lichen planus (OLP) were identified both clinically and confirmed histologically (in atypical cases) so that the prevalence of oral lichen planus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 23 publications
(34 reference statements)
6
44
1
2
Order By: Relevance
“…As other authors had prior (Ingafou, Leao, Porter, & Scully, ; Lauritano et al, ; Mostafa & Ahmed, ; Xue et al, ), we found a higher incidence of OLP in women (85.4%). A possible reason for this association could be that women have greater genetic, neuronal and psychological predisposition to developing depressive or anxious episodes (Ramsey et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…As other authors had prior (Ingafou, Leao, Porter, & Scully, ; Lauritano et al, ; Mostafa & Ahmed, ; Xue et al, ), we found a higher incidence of OLP in women (85.4%). A possible reason for this association could be that women have greater genetic, neuronal and psychological predisposition to developing depressive or anxious episodes (Ramsey et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…The diagnostic method of DM adopted is unknown in ten articles (Barbosa et al, ; Bastos et al, ; Borghelli, Pettinari, Chuchurru, & Stirparo, ; Chung et al, ; Guggenheimer et al, ; Kövesi & Bánóczy, ; Mostafa & Ahmed, ; Saini et al, ; Sousa et al, ; Xue et al, ); five have established the diagnosis of DM by conducting the FPG test (Atefi et al, ; Denli et al, ; Mohsin, Ahmed, Fawwad, & Basit, ; Petrou‐Amerikanou et al, ; Van Dis & Parks, ). Seven articles include DM type 2 (Al‐Maweri, Ismail, Ismail, & Al‐Ghashm, ; Bastos et al, ; Cristina de Lima, Nakata, Balducci, & Almeida, ; Denli et al, ; Mohsin et al, ; Romero et al, ; Sousa et al, ), two DM type 1, and two include both DM types (Petrou‐Amerikanou et al, ; Saini et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lichenoid reactions, clinically indistinguishable from OLP (van der Waal, ), can be induced by antihyperglycemic and antihypertensive drugs (Kaomongkolgit, ), two of the most common medications among diabetic patients. Of all the articles studied in this review, there are three (Guggenheimer et al, ; Petrou‐Amerikanou et al, ; Van Dis & Parks, ) that take into account the medication of their patients; and four studies (Mostafa & Ahmed, ; Romero et al, ; Seyhan et al, ; Xue et al, ) do not include those patients suspected of undergoing lichenoid reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A reported prevalence of 1.27% commonly in women aged between 30 and 60 years (1). In a recent study in Egypt revealed a prevalence of 1.43% among the Egyptians (2). OLP are mostly polymorphic such as reticular type which is present as white striae known as Wickham’s striae often bilateral and asymptomatic.…”
Section: Introductionmentioning
confidence: 99%